Dasar-Dasar Strategi Humor Indonesia Memanfaatkan Pengalaman Berbahasa Cak Lontong - Yuwana, Rawuh Yuda; Santosa, Riyadi; Sumarlam, Sumarlam (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2019)
The purpose of this research is to find a strategy for Indonesian humor material by Cak Lontong. This research is a qualitative descriptive study. The data was collected using the method of referring to the basic tapping techniques and advanced note-taking techniques. Data analysis in this study uses a referential equivalent method with similar linking techniques to support codification, reduction, presentation, and interpretation under a qualitative research framework. The results of this study showed that Cak Lontong used eight humor strategies namely utilizing general truths that are clearly known to people, changing constituents with language experience, deliberately misplacing pronouns, conveying something that is incomplete, changing different languages, giving responses that are unrelated, utilizing language gaps to distort their meaning, and conveying unfair, absurd, or even controversial topic.